Unemployment in Kazakhstan and identifying its causes - Хитахунов, А. (Journal of Economic Research & Business Administration, 2015)
The article considers the main problems in the labor market . In particular, we studied the main causes of unemployment in the Kazakhstan. Message from the President "Socio-economic modernizatsiya- main vector of development of Kazakhstan " considered to be one of the solutions to the problem of employment . He noted that for the realization of its important role of the Government and society.